21st Century Skills in Practice: Malaysian Trainee Teachers’ Experience at Managing Students’ Learning during the Pandemic - Norhaili Massari; Noor Saazai Mat Saad; Fariza Puteh Behak; Sakinah Ahmad; Suzanah Selamat; Hazlina Abdullah; Haliza Harun; Normazla Ahmad Mahir; Hazleena Baharun (USIM Press, 2024)
Teaching practicum is an essential part of teacher-training that provides real classroom engagement for a beginner teacher. It is considered as one of the most critical components of teacher preparation with the greatest impact on teacher quality (Mtika, 2011; Zeichner, 2010; Graham, 2006; Tang, 2003) and is significant for the development of their pedagogical skills (Kauffman, 1992). The sudden upsurge of the Covid -19 infections around the world in the first quarter of 2020, witnessed massive closure of schools worldwide in order to contain the spread of the pandemic. This unexpected turn of events had flipped the more traditional face-to-face method of teaching and learning into distance learning that requires 21st. Century technology and skills. This paper explores the experience of a group of trainee teachers from an institute of higher learning in Malaysia, at managing this unprecedented challenge in delivering education remotely via technology. Data were collected from interviews and supplemental written records in the form of lesson plans, teaching evidence, and online tools employed for teaching and learning. The findings show that the trainee teachers undergo varied and often challenging experiences in ensuring the continuity of curriculum-based education and the students’ progress in learning. Their successes in delivering the lessons amidst the novel encounters are the epitome of resilient and flexible teachers in the making.